Bringing math students into the formative assessment equation : tools and strategies for the middle grades - Creighton, Susan Janssen; Tobey, Cheryl Rose; Karnowski, Eric; Fagan, Emily R. (Corwin, a SAGE Company, 2015)
Make formative assessment work for you-and your math students! Finally, formative assessment that adds up! Bringing Math Students Into the Formative Assessment Equation is the ultimate resource for helping teachers implement formative assessment in the middle school mathematics classroom. And it's much more than that. With this research-based, teacher-tested guide, you won't just learn effective teaching strategies-you'll turn your students into self-regulated learners. They'll monitor and assess their own progress-and communicate to you about it! Features include: *A clear and manageable six-aspect instructional model *Detailed strategies for helping students own their successes *Real-life examples from middle school mathematics teachers *Useful resources and a companion website to help you implement formative assessment in your classroom Formative assessment isn't just for teachers anymore. With the help of ...